2005
DOI: 10.1038/sj.gt.3302465
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of DNA vaccine during chemotherapy on reactivation and reinfection of Mycobacterium tuberculosis

Abstract: Active disease of tuberculosis (TB) can be developed decades later by either a relapse of the initial infection (endogenous reactivation) or by an entrance of the secondary infection (exogenous reinfection), since the current chemotherapy cannot lead to complete elimination of tuberculosis. Although the immunotherapeutic approaches in conjunction with conventional chemotherapy were tried to prevent TB growth via boosting the immune system, their therapeutic effects are still controversial. Here, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…The immunotherapeutic effect of PstS3 is consistent with the previous reports. 15 In contrast, another group showed that PstS3 DNA vaccination reduced CFU from 8 to 12 weeks after infection. 8 This discrepancy may be attributed to varying experimental conditions, such as challenge route (intravenous vs aerosol), antigen engineering (PstS3 vs F-PstS3) and protocols.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The immunotherapeutic effect of PstS3 is consistent with the previous reports. 15 In contrast, another group showed that PstS3 DNA vaccination reduced CFU from 8 to 12 weeks after infection. 8 This discrepancy may be attributed to varying experimental conditions, such as challenge route (intravenous vs aerosol), antigen engineering (PstS3 vs F-PstS3) and protocols.…”
Section: Discussionmentioning
confidence: 96%
“…We previously demonstrated that Ag85A and PstS3 DNA vaccinations completely block TB reactivation, and significantly prevent secondary infection when combined with chemotherapy. 15 In contrast, reduction of bacterial loads by MPT64 DNA vaccination was not significant compared with that in control mice. 16 As there are no general criteria for defining protective antigens from different vaccination protocols, a comparative study between TB antigens and M. tuberculosis exposure models under a single experimental condition is essential.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…12 A double-gene DNA vaccine composed of Ag85A and PstS-3 genes could reduce bacterial growth better than the single-gene DNA vaccines during the period of chemotherapy after a secondary reinfection. 13 Therapeutic effects of Ag85B and MPT64 DNA vaccines indicated that Ag85B DNA vaccination had immunotherapeutic effects on TB in mice, whereas MPT64 DNA did not. 15 More importantly, it seems that the timing of DNA vaccination may be a major factor in determining the efficacy of the vaccine in a latent model because DNA vaccination against TB may minimize granuloma formation and/or necrosis induction when simultaneously combined with chemotherapy; DNA vaccine-induced Th1 and cytotoxic T-lymphocyte responses may act together with chemotherapy to eliminate M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%
“…Prophylactic DNA vaccines expressing various M. tuberculosis antigens, including Ag85A, Ag85B, MTP-64, ESAT-6, 65-kDa heat-shock protein and PstS-3, were found to be effective at limiting the growth of M. tuberculosis in heavily infected mice. [11][12][13][14] After the completion of chemotherapy in mice infected with M. tuberculosis intravenously, vaccination with plasmid DNA expressing 65-kDa heat-shock protein was effective in preventing reactivation. 14 Ag85A DNA vaccine, when simultaneously administered with chemotherapy, could effectively prevent reactivation of aerogenically transmitted M. tuberculosis.…”
Section: Introductionmentioning
confidence: 99%